قياس وتحليل أثر التنويع الاقتصادي على النمو الاقتصادي باستخدام نماذج بنال حالة الدول العربية المصدرة للنفط أوبك للفترة 2000-2020 - جاوي, فايزة; حفصي بونبعو, ياسين (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى قياس وتحليل أثر التنويع الاقتصادي على النمو الاقتصادي في البلدان العربية المصدرة للبترول "أوبك"، باستخدام نماذج بنال لعينة من ستة دول خلال الفترة 2000-2020، ضمت الدراسة مؤشرات التنويع الاقتصادي والمستوى العام لأسعار النفط كمتغيرات مستقلة واستخدام معدل النمو الاقتصادي كمتغير تابع. توصلت الدراسة في شقها التحليلي إلى ضعف درجة التنويع الاقتصادي باستثناء نموذج الإمارات الذي اظهر نتائج إيجابية، أما بالنسبة للجانب القياسي تبّين أن نموذج التأثيرات الفردية الثابتة هو الملائم، وتبين أيضا الريع النفطي ممثل بمستوى عام لأسعار النفط ومؤشرات التنويع الاقتصادي له تأثير معنوي وموجب على النمو الاقتصادي. The objective of this study is to measure and analyse the impact of economic diversification on economic growth in the oil exporting Arab countries of OPEC, using sample Panel models from six countries during the period 2000-2020، The study included indicators of economic diversification, the overall level of oil prices as independent variables and the use of the economic growth rate as a dependent variable. In its analytical analysis, the study found a low degree of economic diversification except for the UAE model, which showed positive results. For the index side, the fixed individual impact model is appropriate, as well as oil rents represented by an overall level of oil prices and indicators of economic diversification have a moral and positive impact on economic growth
Measuring and analysing the impact of Economic Diversification on Economic Growth using Panel Model, case of OPEC Oil Exporting Arab Countries 2000-2020
مقال
Keywords: التنويع اقتصادي، النمو الاقتصادي، نماذج بنال، دول الأوبك; economic diversification, economic growth, Panel models, OPEC countries.